2013
DOI: 10.2478/pbj-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented euglenophytes of the genera Euglena, Euglenaria, Lepocinclis, Phacus and Monomorphina from the southeastern United States

Abstract: abstract:The biogeography and taxonomy of euglenophytes from the southeastern United States were studied in material from lakes, ponds and rivers of Alabama, Georgia, Kentucky, Mississippi, North Carolina and Tennessee. The 68 taxa found, 26 of which are new for this region, belong to the genera Euglena (26 taxa), Euglenaria (2), Lepocinclis (13), Phacus (25) and Monomorphina (2). The taxa occurred at low density, sometimes as a single specimen. Euglenophyte diversity was highest in ponds; rivers had the fewes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…All these taxa have a cosmopolitan distribution and are known to thrive in moderately to highly polluted waters rich in organic matter (Wołowski 2011;Duangjan et al 2014;Triemer & Zakryś 2015). Our results confirm that these euglenoids usually prefer, and proliferate in, warm and stagnant waterbodies (e.g., Wołowski 1998, Ciugulea & Triemer 2010Wołowski et al 2013;Shaaban et al 2015;Varol & Şen 2016). These habitat conditions are observed mainly in two of the three studied habitats: Abu Nuss Lake and the agricultural drainage, which showed high concentrations of N and P compounds (see Table 1 for more details).…”
Section: Resultssupporting
confidence: 76%
“…All these taxa have a cosmopolitan distribution and are known to thrive in moderately to highly polluted waters rich in organic matter (Wołowski 2011;Duangjan et al 2014;Triemer & Zakryś 2015). Our results confirm that these euglenoids usually prefer, and proliferate in, warm and stagnant waterbodies (e.g., Wołowski 1998, Ciugulea & Triemer 2010Wołowski et al 2013;Shaaban et al 2015;Varol & Şen 2016). These habitat conditions are observed mainly in two of the three studied habitats: Abu Nuss Lake and the agricultural drainage, which showed high concentrations of N and P compounds (see Table 1 for more details).…”
Section: Resultssupporting
confidence: 76%
“…Dominance of these genera in the water bodies indicates their strong eutrophication [50,70]. They are common in small water bodies, rich in organic matter [71,72], as well as dammed reservoirs [73].…”
Section: Discussionmentioning
confidence: 99%
“…EC & pH were measured by using (pH-EC-TDS meter, HI 9812, Hanna instrument). [24][25][26] . The most abundant genera in this study was Euglena, Lepocinclis, Phacus and Trachelomonas identified in most sites, while two species Lepocinclis salina and Euglena stellate confined with high total dissolved solids and more saline water found in Nawkand, Chemma and Azarian springs.…”
Section: Sample Collection and Identification Of Algaementioning
confidence: 99%